HIV Treatment Outcomes in POP-UP: Drop-in HIV Primary Care Model for People Experiencing Homelessness . (27th June 2022) - Hickey, Matthew D; Imbert, Elizabeth; Appa, Ayesha; Del Rosario, Jan Bing; Lynch, Elizabeth; Friend, John; Avila, Rodrigo; Clemenzi-Allen, Angelo; Riley, Elise D; Gandhi, Monica; Havlir, Diane V
Abstract: Background: People with HIV experiencing homelessness have low rates of viral suppression, driven by sociostructural barriers and traditional care system limitations. Informed by the capability-opportunity-motivation-behavior (COM-B) model and patient preference research, we developed POP-UP, an integrated drop-in (nonappointment-based) HIV clinic with wrap-around services for persons with housing instability and viral nonsuppression in San Francisco. Methods: We report HIV viral suppression (VS; <200 copies/mL), care engagement, and mortality at 12 months postenrollment. We used logistic regression to determine participant characteristics associated with VS. Results: We enrolled 112 patients with viral nonsuppression and housing instability: 52% experiencing street-homelessness, 100% with a substance use disorder, and 70% with mental health diagnoses. At 12 months postenrollment, 70% had ≥1 visit each 4-month period, although 59% had a 90-day care gap; 44% had VS, 24% had viral nonsuppression, 23% missing, and 9% died (6 overdose, 2 AIDS-associated, 2 other). No baseline characteristics were associated with VS. Conclusions: The POP-UP low-barrier HIV care model successfully reached and retained some of our clinic's highest-risk patients. It was associated with VS improvement from 0% at baseline to 44% at 12 months among people with housing instability. Care gaps and high mortality from overdose remain major challenges to achieving optimal HIV treatment outcomes in this population.